2013
DOI: 10.1371/journal.pone.0059325
|View full text |Cite
|
Sign up to set email alerts
|

Heritability and Fitness Correlates of Personality in the Ache, a Natural-Fertility Population in Paraguay

Abstract: The current study assessed the heritability of personality in a traditional natural-fertility population, the Ache of eastern Paraguay. Self-reports (n = 110) and other-reports (n = 66) on the commonly used Big Five Personality Inventory (i.e., extraversion, agreeableness, conscientiousness, neuroticism, openness) were collected. Self-reports did not support the Five Factor Model developed with Western samples, and did not correlate with other-reports for three of the five measured personality factors. Heritab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 52 publications
1
18
1
1
Order By: Relevance
“…With such simple rules in place, our model shows how increasing the number of niches in a population environment can reduce the correlations between personality attributes, and in turn increase the number of emergent factors required to explain patterns of behavioral covariance. These simulation results expand the scope of existing cross-cultural studies that focus on explaining variation in personality trait values [13,14,15,16,35], to address broader questions concerning cross-cultural variability in personality structure. In addition, niche diversity potentially offers a consilient way in which to think about disparate descriptors of societal complexity.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…With such simple rules in place, our model shows how increasing the number of niches in a population environment can reduce the correlations between personality attributes, and in turn increase the number of emergent factors required to explain patterns of behavioral covariance. These simulation results expand the scope of existing cross-cultural studies that focus on explaining variation in personality trait values [13,14,15,16,35], to address broader questions concerning cross-cultural variability in personality structure. In addition, niche diversity potentially offers a consilient way in which to think about disparate descriptors of societal complexity.…”
Section: Discussionmentioning
confidence: 60%
“…To date, the vast majority of data collected to generate structural models of personality comes from large, modern, industrialized societies. Yet, the five factor structure has failed to replicate when tested within smaller-scale societies [12,13,14], in several low income country samples [15], or across a more inclusive set of natural lexicons [16]. Moreover, while many studies have looked at cultural differences in levels of specific traits (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Among men, greater manifest extraversion is consistently positively correlated with reproductive success within both small-scale subsistence societies (Alvergne et al, 2010;Bailey et al, 2013;Gurven et al, 2014) and modern industrialized societies (Berg, Lummaa, Lahdenpera, Rotkirch, & Jokela, 2014;Jokela, 2012). Among women, greater extraversion is less strongly associated with reproductive success within small-scale societies (Alvergne et al, 2010;Bailey et al, 2013;Gurven et al, 2014), but has shown positive association with reproduction in modern societies (Berg et al, 2014;Jokela, 2012).…”
Section: Cost-benefit Tradeoffs Along the Extraversion Continuummentioning
confidence: 98%
“…Among rural Senegalese farmers, extraverted men and women with intermediate levels of neuroticism have more children (Alvergne et al, 2010). Among Ache forager-farmers, extraverted men have more children (Bailey et al, 2013). Both studies, however, have small sample sizes, do not consider potential costs of specific dispositions, nor whether dispositions co-vary with observed fitness-related behavior.…”
Section: Introductionmentioning
confidence: 99%